Penanaman Karakter Religius Melalui Metode Pembiasaan - Siswanto Siswanto; Ifnaldi Nurmal; Syihab Budin (AR-RIAYAH: Jurnal Pendidikan Dasar)
This research is to describe how to cultivate religious character education through the habituation method. The type of research is qualitative in which the approach used is descriptive qualitative. Furthermore, the data obtained by interview, observation and documentation. Furthermore, the analysis was carried out by reducing data, displaying data, and drawing conclusions. The research shows that the cultivation of religious character education through habituation methods can be carried out such as routine activities, namely dhuha prayer, murojaah and tadarus al-quran before lessons start and zhuhur prayer in congregation at school.